Mismatch Negativity But Not P300 Is Associated With Functional Disability in Schizophrenia. (3rd August 2017) - Hamilton, Holly K; Perez, Veronica B; Ford, Judith M; Roach, Brian J; Jaeger, Judith; Mathalon, Daniel H
Abstract: Mismatch negativity (MMN) and P300 event-related potential (ERP) reductions in schizophrenia (SZ) reflect preattentive and attention-mediated auditory processing deficits, respectively. Although both have been linked to cognitive deficits in SZ, their relative contributions to real-world functioning are unclear. We sought to determine the functional significance of disrupted auditory processing in SZ by examining MMN and P300 in typically disabled low-functioning patients and in patients with high levels of independent role functioning. MMN to auditory deviants and P300 to infrequent auditory target and nontarget novel stimuli were assessed in 20 high-functioning SZ patients (HF-SZ), 17 low-functioning patients (LF-SZ), and 35 healthy comparison (HC) subjects. There was a group effect on MMN and P300 amplitudes across stimulus types. MMN was significantly diminished in LF-SZ compared to HF-SZ and HC, and HF-SZ demonstrated comparable MMN to HC. In contrast, P300 was significantly reduced in both LF-SZ and HF-SZ compared to HC. Logistic regression suggested independent sensitivity of MMN to functioning in SZ over and above P300 measures. Neither MMN nor P300 were associated with positive or negative symptom severity. Results replicate MMN and P300 abnormalities in SZ, and also suggest that the neural mechanisms associated with the preattentive detection of auditory deviance are most compromised in patients with functional disability. MMN may index pathophysiological processes that are critical for optimal functioning in SZ.